Effect of Self-etching Adhesives on the Bond Strength of Glass-Ionomer Cements. - Zahra Jaberi Ansari (Frontiers in Dentistry, 2014)
Adequate bond strength between glass ionomer cements and composite resin is necessary for the success of the sandwich technique.This study assessed the micro-shear bond strength of composite resin to glass-ionomer cements (GIC) using self-etch adhesives with different pH values.One hundred specimens (6×4×2 mm) were made using Fuji II and Fuji II LC GICs and treated with different adhesives as follows: Group 1:Fuji II+ Adper Prompt L-Pop, Group-2: Fuji II+SE bond, Group-3: Fuji II + AdheSE, Group-4:Fuji II+ Protect bond, Group-5: Fuji II + Single bond, Group-6:Fuji II LC+ Adper Prompt LPop, Group-7: Fuji II LC+SE bond, Group-8:Fuji II LC+ AdheSE, Group-9: Fuji II LC+ Protect bond, and Group-10: Fuji II LC+ Single bond. Each group consisted of 10 specimens. A cylinder of Z100 composite resin was placed on each sample and light cured. After 24 hours of water storage (37°C), the specimens were subjected to micro-shear bond strength tests (0.5 mm/min). Data were analyzed using two-way ANOVA and Tukey's test.The mean micro-shear bond strength of groups 1-10 was 11.66±1.79, 16.50±1.85, 18.47±1.77, 13.95±1.77, 15.27±1.49, 15.14±0.90, 20.03±1.19, 17.48±3.00, 16.24±1.98 and 16.03±1.49 MPa, respectively. There were significant differences between groups 1 and 7 (P0.05). Fuji II LC showed higher bond strength than Fuji II (P